PENGARUH LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS HIGHER ORDER THINKING SKILL (HOTS) TERHADAP HASIL BELAJAR TEMATIK PESERTA DIDIK - Almira Darlin; Rarasaning Satianingsih; Cholifah Tur Rosidah (Lembaga Pengembangan Kinerja Dosen, 2022)
This research is motivated by the importance of HOTS-based student worksheets in thematic learning. HOTS-based student worksheets were used in this study with the aim of actively interacting between teachers and students as well as students and students as well as improving learning outcomes and increasing students' higher-order thinking skills. The goal to be achieved in this study is to find out the thematic learning outcomes of students before and before being treated with HOTS-based student worksheets. This study uses experimental quantitative research on fourth grade students at State Elementary School. Dr.Sutomo V/327 Surabaya with a population of 281 students evenly distributed in 8 classes. The sampling technique in this study used a post-test only control group design technique. The research sample was students in grades IV A - IV H. The experimental class of learning using HOTS-based thematic worksheets and the control class were given lessons as is usually done in schools in the form of lectures and given demonstrations. The research was conducted at the public elementary school of Dr. Sutomo V/327 Surabaya. The research instrument used is a test (posttest). The results showed that the learning outcomes of students had increased by using the HOTS-based student worksheets in thematic learning Theme 3 Sub Theme 2 Learning 1 State elementary school students Dr. Sutomo V/327 Surabaya based on One Way Anova test with sig. less than 0.05.